Antiplatelet therapy in the era of drug-eluting stents: current and future perspectives. (September 2007) - Ducrocq, Gregory; Serebruany, Victor; Tanguay, Jean-Francois
The use of drug-eluting stents (DESs) dramatically reduced in-stent restenosis. However, the increasing use of these stents has raised concern about their potential thrombogenicity. Indeed, the particularity of DES thrombosis compared with bare metal stent thrombosis is a high rate of late thrombosis. Antiplatelet therapy is efficient in preventing DES thrombosis. However, this therapy could be optimized and may be improved in the future. This article will review the mechanisms and the epidemiology of stent thrombosis. Then, we will summarize the antiplatelet therapeutic strategies used to prevent stent thrombosis and especially DES-associated thrombosis. Finally, we will present some data with regard to potential advantages and pitfalls in DES thrombosis prevention using novel antiplatelet agents currently under development, as well as future stent designs with improved healing properties.